Differences in body composition, static balance, field test performance, and academic achievement in 10–12-year-old soccer players - Hermassi, Souhail; Hayes, Lawrence D.; Bartels, Thomas; Schwesig, René (Frontiers in Physiology, 2023)
This study aimed to compare 10-12-year-old Qatari male soccer players (n=45) regarding different dimensions (anthropometric, academic and physical performance). Anthropometric parameters (body mass, fat percentage (%BF), body mass index (BMI)) academic achievement (mathematics and science grade point average [GPA]) and physical performance (Yo-Yo Intermittent Recovery Test (level 1), squat jumps (SJ), counter-movement jumps (CMJ), stork balance test, 10 and 15 m sprint tests, T-half test for change-of-direction (CoD) ability, hand-grip strength, medicine ball throw (MBT)). Schoolchild soccer players were divided into three groups: 12-year-old players (U12; n = 16), 11-year-old players (U11; n = 14), 10-year-old players (U10; n = 15). Apart from mathematics, Yo-Yo IR1 and 10 m sprint, all performance parameters showed significant age effects. The largest age-related difference was observed for 15 m sprint (p < 0.001). Both adjacent age groups displayed significant differences for 15 sprint (U10 vs. U11: p = 0.015; U11 vs. U12: p = 0.023). Concerning academic performance, a significant age effect was found for science (p < 0.001). There was a main age effect on academic performance difference between U10 and U11 (p = 0.007). Academic parameters did not correlate with any physical performance parameter or anthropometric parameter. The strongest correlations were detected for body height and agility T-half test (r =-0.686) and medicine ball throw (r = 0.637). The biological maturity was strongly correlated with handgrip strength (r = -0.635). In conclusion, soccer coaches and physical education teachers can use these data as reference values for evaluation of school-aged soccer players, and for ascertaining specific training targets. Obviously, short sprinting ability and aerobic capacity are not functions of age and need a specific training for significant improvements.